Debt to GDP Ratio and inflation from the perspective of Functional Finance Theory and MMT - Tanaka, Yasuhito (Business and Economic Research, 2022)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">This paper will examine the relationship between budget deficit, inflation rate and debt to GDP ratio from the perspective of Functional Finance Theory and MMT (Modern Monetary Theory). Using a basic macroeconomic model in which the interest rate of government bonds is endogenously determined, with overlapping generations model in mind, mainly, we show the following results. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">1. If the proportion of the savings consumed is smaller than one, the larger the budget deficit is, the larger the inflation rate is. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">2. If the proportion of the savings consumed is smaller than one, the larger the inflation rate is, the smaller the debt to GDP ratio is. Therefore, excessive budget deficits cause inflation, which results in a smaller debt to GDP ratio. A large budget deficit is not associated with a high debt to GDP ratio. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">3. The larger the budget deficit is, the weaker the condition on the proportion of savings that is consumed in order for the debt to GDP ratio not to diverge is.